2020
DOI: 10.3126/jbs.v7i1.29851
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance among Gram-negative isolates in Nepal: A review

Abstract: Background: Colistin resistance among Gram-negative isolates is a tremendous public health problem, and there are very few studies in Nepal about these pathogens. Hence, this review provides comprehensive data on colistin resistance among Gram-negative isolates from various samples in Nepal. Methods: Articles reporting colistin resistance among various Gram-negative isolates from Nepal before July 2019 were selected; analyzed and relevant data was collected. Results: Colistin resistance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…A similar high level of colistin resistance (23.1%) was observed in the same hospital among E. coli isolated from urine samples [50]. Overall, the rate of colistin resistance was higher when compared with other reported cases in other countries [51][52][53]. A study from the worldwide SEN-TRY antimicrobial surveillance program reported that resistance to polymyxins is stable for most Gram-negative pathogens except for Klebsiella species.…”
Section: Discussionsupporting
confidence: 54%
“…A similar high level of colistin resistance (23.1%) was observed in the same hospital among E. coli isolated from urine samples [50]. Overall, the rate of colistin resistance was higher when compared with other reported cases in other countries [51][52][53]. A study from the worldwide SEN-TRY antimicrobial surveillance program reported that resistance to polymyxins is stable for most Gram-negative pathogens except for Klebsiella species.…”
Section: Discussionsupporting
confidence: 54%
“…colistin are now used as a last line drugs to treat such emerging pathogens [ 2 , 5 ]. However, colistin resistant P. aeruginosa is also being reported recently that is in increasing trend globally [ 6 ]. Similarly, in P. aeruginosa along with carbapenem and colistin resistant genes, overexpression of efflux pump is also one of the intrinsic mechanism that is serving them to develop into superbugs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them most common type in P. aeruginosa is NDM type; as it is located in plasmid and have a high global dissemination rate [ 8 , 9 ]. Likewise, in Nepal, the prevalence of colistin resistant P. aeruginosa has increased to 2.8% [ 6 ]. Resistance to colistin in bacterial species can be either intrinsic type or acquired via chromosomal mutation or genes carried on plasmid [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only about one-fourth of the total samples showed bacterial growth positivity. The common isolates were Gram-negative because the infection caused by the group is predominant in hospital settings 35 , 36 and their persistence in community settings is also reported. 37 The majority of them were E. coli (n = 77) since the organism is frequently associated with nosocomial and community-acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of colistin resistance exhibited by E. coli from food-producing animals in Nepal is a major concern. 15 , 35 This indicates a high possibility of zoonotic transmission of this resistance to humans resulting in increased prevalence in clinical isolates. 52 , 53 In our experiments, the MIC value of colistin was demonstrated up to 16 g/L.…”
Section: Discussionmentioning
confidence: 99%